The Role of Status and Friendly Performance in the Formation of Higher Education Students 'Culture - Sardorbek Abdullaev (Research Parks Publishing LLC, 2021)
The article deals with the rich musical heritage of the Uzbek people with a long history. A comparative analysis of the classical music culture of the East.